2011
DOI: 10.2478/v10099-011-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Competencies in an Ontology-Based Framework Supporting Teachers to Construct Learning Designs in the Domain of Sustainable Energy Education

Abstract: Integration of Competencies in an Ontology-Based Framework Supporting Teachers to Construct Learning Designs in the Domain of Sustainable Energy Education In previous work, a framework based on three ontologies (content, learning design and sustainable energy domain models) was introduced in order to support teachers to construct learning designs in the field of sustainable energy education. This paper is focusing on the integration of a competency model in the structure of this framework. This model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Forsyth (1997) studied on the construction and validation of an instructional systems design model for community-based train-the-trainer instruction by using the Developmental research Phase 3 and found the efficiency of the ISD models and programming TtT. Karetsos and Haralambopoulos (2011) studied on the integration of competencies in an ontologybased framework supporting teachers to construct learning designs in the domain of sustainable energy education. Nattaphon (2011) studied on the development model of knowledge management via webbased learning to enhance pre-.…”
Section: Discussionmentioning
confidence: 99%
“…Forsyth (1997) studied on the construction and validation of an instructional systems design model for community-based train-the-trainer instruction by using the Developmental research Phase 3 and found the efficiency of the ISD models and programming TtT. Karetsos and Haralambopoulos (2011) studied on the integration of competencies in an ontologybased framework supporting teachers to construct learning designs in the domain of sustainable energy education. Nattaphon (2011) studied on the development model of knowledge management via webbased learning to enhance pre-.…”
Section: Discussionmentioning
confidence: 99%